Varying levels of susceptibility to late blight in Ecuador - Knutsson, Jenny (2011)
Potato late blight is a devastating disease in potato production all over the world and constitutes the major biological yield limiting factor in Ecuador. The disease is generally controlled chemically and a large proportion of the total potato production cost in Ecuador is due to fungicides. Potato late blight is also controlled by disease escape. A third alternative when it comes to protecting the crop from late blight is to cultivate varieties resistant to the disease. However, most Ecuadorian farmers still use varieties with a high susceptibility to late blight. Furthermore even resistant varieties are frequently treated with large amounts of fungicides, often due to lack of knowledge about the adequate amount needed. Successful disease management is a very important factor in order to increase productivity and reduce production costs for resource-poor farmers, and one part of this is to quantify the amount of fungicide application needed for different varieties of potato. In this experiment field trials with 12 varieties of potato were performed in Quito, Ecuador. A recently developed scale was used to evaluate the level of susceptibility to potato late blight among the different varieties. The results provided new information about some of the potato cultivars and may lead to an increased cultivation of varieties with a higher level of resistance to the disease.